Data Protection in E-Voting Systems: The 2024 Nigerian Bar Association’s Elections in Retrospect - Babalola, Olumide (ABUAD Law Journal, 2025)
The adoption of e-voting systems in democratic processes necessitates a robust data protection framework to ensure voter privacy, electoral integrity, and compliance with data protection laws. This article critically examines data protection and privacy concerns in e-voting, with a focus on the 2024 Nigerian Bar Association (NBA) elections. Key issues explored include informed consent, confidentiality and integrity threats, cross-border data transfers, data minimization, data retention, and transparency. The article also highlights privacy and data protection challenges specific to NBA e-voting, such as the publication of the voters’ list, post-election access to servers and application logs, and the consent of voters to the sharing of election transactions. To address these concerns, the article proposes practical recommendations, including proactive disclosure of voters’ personal data usage, a multi-layered approach to combating identity theft and double voting, recognition of votes cast as personal data subject to Data Subject Access Requests (DSARs), enhanced protection of international users’ data, and the need for auditable and transparent electoral processes. By advocating for a more accountable and privacy-conscious approach to e-voting, this article contributes to the ongoing discourse on balancing electoral transparency with data protection imperatives.